Impact of organ motion on volumetric and dosimetric parameters in stomach lymphomas treated with intensity‐modulated radiotherapy. Issue 8 (10th August 2019) - Uchinami, Yusuke; Suzuki, Ryusuke; Katoh, Norio; Taguchi, Hiroshi; Yasuda, Koichi; Miyamoto, Naoki; Ito, Yoichi M.; Shimizu, Shinichi; Shirato, Hiroki
Abstract: Purpose: Interplay effects may influence dose distributions to a moving target when using dynamic delivery techniques such as intensity‐modulated radiotherapy (IMRT). The aim of this study was to evaluate the impact of organ motion on volumetric and dosimetric parameters in stomach lymphomas treated with IMRT. Methods: Ten patients who had been treated with IMRT for stomach lymphomas were enrolled. The clinical target volume (CTV) was contoured as the whole stomach. Considering interfractional uncertainty, the internal target volume (ITV) margin was uniformly 1.5 cm to the CTV and then modified based on the 4DCT images in case of the large respiratory motion. The planning target volume (PTV) was created by adding 5 mm to the ITV. The impact of organ motion on the volumetric and dosimetric parameters was evaluated retrospectively (4D simulation). The organ motion was reproduced by shifting the isocenter on the radiation treatment planning system. Several simulation plans were created to test the influence of the beam‐on timing in the respiration cycle on the dose distribution. The homogeneity index (HI), volume percentage of stomach covered by the prescribed dose (Vp ), and D99 of the CTV were evaluated. Results: The organ motion was the largest in the superior‐inferior direction (10.1 ± 4.5 mm [average ± SD]). Stomach volume in each respiratory phase compared to the mean volume varied approximately within a ± 5% range in most of the patients. The PTV margin was sufficiently large to cover the CTV during the IMRT. There was a significant reduction in Vp and D99 but not in HI in the 4D simulation in free‐breathing and multiple fractions compared to the clinically‐used plan ( P  < 0.05) suggesting that interplay effects deteriorate the dose distribution. The absolute difference of D99 was less than 1% of the prescribed dose. Conclusions: There were significant interplay effects affecting the dose distribution in stomach IMRT. The magnitude of the dose reduction was small when patients were treated on free‐breathing and multiple fractions.